Roots of counterterrorism : contemporary wisdom from Dutch intelligence - Hijzen, Constant, 1982- 1982- (Causes and consequences of terrorism series, 2024)
"On 22 March 1979, at 09:00 in the morning, the British ambassador to the Netherlands Sir Richard Sykes and his butler Karel Straub were killed in front of the ambassador's residence, called the Spaansche Hof (Spanish court). Immediately after the lethal shots were fired, the police unit of The Hague, assisted by police units specialised in counterterrorism and the Dutch security service BVD (Binnenlandse Veiligheidsdienst), commenced their investigation. In an overview of terrorist events in March/April 1979, a special terrorism unit of the Dutch police reported the following details about the events:"--